The Effects of E-Portfolio Implementation on Motivation in an Online Collaborative Learning Setting - Erten, Pınar; Ozdemir, Oguzhan; Kazu, İbrahim Yaşar (My University, 2019)
The purpose of this study was to determine the effects of e-portfolio implementation in an Operating Systems and Applications course on students’ motivations in an online collaborative learning setting. The differences between motivation pre-test and post-test scores of the experimental and control groups were examined. Student opinions were also analyzed. Qualitative and quantitative data were collected together. The experimental group consisted of 35 students and the control group consisted of 33 students. Only the experimental group students’ opinions were gathered for the qualitative aspect of the study. The study was conducted through the course web-site and within the virtual classroom setting. Motivation was observed to be high before the implementation on the experimental group and after the implementation on the control group. In addition, while there were no changes in the motivation levels of the experimental group before and after the implementation, according to before the implementation, a decrease in control group motivation was observed after the implementation. Also, students were observed to state motivation decreased as reported on the qualitative dimension of the study. These two results supported each other. The course settings, which can minimize or annihilate the factors stated by the students that caused motivation decreases, should be reorganized and students should be sufficiently informed. Settings that support each other should be designed through face-to-face education opportunities in virtual and online systems.
Keywords: Eğitim; Eğitim Araştırmaları; Bilgisayar Bilimleri; Bilgi Sistemleri; Bilgisayar Bilimleri; Teori ve Metotlar